Pengaruh plunge depth dan preheat terhadap sifat mekanik sambungan friction stir welding polyamide - Budy Nugroho; Triyono .; Nurul Muhayat (Jurnal Teknik Mesin Indonesia, 2016)
Friction stir welding is a joining method that utilizes heat caused by the friction between workpiece material and pin. It employs several parameters such as tool rotational speed, welding speed, and plunge depth. The objective of this research is to investigate the effect of plunge depth and preheat on the mechanical properties of friction stir welding polyamide materials. This research used the plunge depths of 5.6 mm, 5.65 mm, 5.7 mm, and 5.75 mm. The parameters maintained to be constant were tool rotational speed of 620 rpm, welding speed of 7.3 mm/minutes, and tool tilt angle of 20. Preheat of 1700C was done as well non preheat method to compare of both methods.The maximum tensile and bending strength was obtained at the tool plunge depth of 5.7 mm with preheat. The value of maximum tensile and bending is 27,3 Mpa, and 75,7 Mpa. The optimization of tool plunge depth and preheat made the stirring better so that the molten material could spread all over weld region. The spreading of the molten material minimized void or defect in the weld region. As a result, the mechanical characteristic of joint increased.